Corporate Criminal Liability Model in The New Criminal Code: Synchronization of The Identification Theory Doctrine With Absolute Liability - Walim Walim; Abdullah Abdullah; Ahmad Faizal Azhar; Sukama Sukama (Sahabat Publikasi, 2026)
Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code) has recognized corporations as subjects of criminal law, marking a significant paradigm shift in the Indonesian criminal law system. However, the regulation of corporate criminal liability in the New Criminal Code still shows a lack of synchronization between the adopted identification theory doctrine and the need for the application of strict liability in the context of certain corporate crimes. This study aims to analyze the model of corporate criminal liability in the New Criminal Code and formulate a synchronization framework between identification theory and strict liability. The research method used is normative juridical with a statutory, conceptual, comparative, and case-based approach. The results show that the New Criminal Code adopts an identification theory-based liability model that requires proof of mens rea for corporate managers. However, this model has significant limitations in addressing complex corporate crimes, particularly in the environmental, occupational health and safety, and capital market sectors. This study found that synchronization is needed through three approaches: first, the application of limited strict liability to certain corporate crimes that are regulatory offenses; second, the development of the vicarious liability doctrine as a bridge between identification theory and strict liability; Third, strengthening the evidentiary mechanism through an organizational liability approach that considers corporate culture and failure to prevent. This synchronization aligns with developments in the UK through the Corporate Manslaughter and Corporate Homicide Act 2007, Australia with its Corporate Criminal Responsibility Model, and the Netherlands with its functional perpetrator approach. Implementing the synchronization model requires harmonization of the New Criminal Code with sectoral laws, strengthening the capacity of law enforcement to understand the complexity of corporate organizations, and developing proportionate and effective corporate criminalization guidelines.